Changes in weight status, quality of life and behaviours of South Australian primary school children: results from the Obesity Prevention and Lifestyle (OPAL) community intervention program - Lucinda Bell; Shahid Ullah; Eva Leslie; Anthea Magarey; Timothy Olds; Julie Ratcliffe; Gang Chen; Michelle Miller; Michelle Jones; Lynne Cobiac (BMC Public Health, 2019)
Abstract Background Childhood obesity is a serious public health concern worldwide. Community-based obesity prevention interventions offer promise due to their focus on the broader social, cultural and environmental contexts rather than individual behaviour change and their potential for sustainability and scalability. This paper aims to determine the effectiveness of a South Australian community-based, multi-setting, multi-strategy intervention, OPAL (Obesity Prevention and Lifestyle), in increasing healthy weight prevalence in 9 to 11-year-olds. Methods A quasi-experimental repeated cross-sectional design was employed. This paper reports on the anthropometric, health-related quality of life (HRQoL) and behaviour outcomes of primary school children (9–11 years) after 2–3 years of intervention delivery. Consenting children from primary schools (20 intervention communities, INT; 20 matched comparison communities, COMP) completed self-report questionnaires on diet, activity and screen time behaviours. HRQoL was measured using the Child Health Utility 9D. Body Mass Index (BMI) z-score and weight status were determined from children’s measured height and weight. A multilevel mixed-effects model, accounting for clustering in schools, was implemented to determine intervention effect. Sequential Bonferroni adjustment was used to allow for multiple comparisons of the secondary outcomes. Results At baseline and final, respectively, 2611 and 1873 children completed questionnaires and 2353 and 1760 had anthropometric measures taken. The prevalence of children with healthy weight did not significantly change over time in INT (OR 1.11, 95%CI 0.92–1.35, p = 0.27) or COMP (OR 0.85, 95%CI 0.68–1.06, p = 0.14). Although changes in the likelihood of obesity, BMI z-score and HRQoL favoured the INT group, the differences were not significant after Bonferroni adjustment. There were also no significant differences between groups at final for behavioural outcomes. Conclusions OPAL did not have a significant impact on the proportion of 9 to 11-year-olds in the healthy weight range, nor children’s BMI z-score, HRQoL and behaviours. Long-term, flexible community-based program evaluation approaches are required . Trial registration ACTRN12616000477426 (12th April 2016, retrospectively registered).